The greenhouse metaphor and the footprint metaphor: climate change risk assessment and risk management seen through the lens of two prominent metaphors - Nerlich, Brigitte; Hellsten, Iina (Institut für Technikfolgenabschätzung und Systemanalyse, 2014)
This article charts the emergence and framing of anthropogenic climate change as risk through the lens of two metaphors: greenhouse effect and carbon footprint. We argue that the greenhouse effect metaphor provided the scientific basis for framing climate change as a risk, indeed it can be seen as part of risk assessment. The carbon footprint metaphor, in turn, can be seen as belonging to the domain of risk management, as through this and other related metaphors, such as carbon offsetting, carbon budgets and the like, policy makers try to act upon the scientific risk assessment delivered by the greenhouse metaphor and encourage human behaviour change that reduces the risks of unmanaged climate change. We investigate how these key metaphors spread both in English news articles and in natural and social science articles and how they may shape current discourses and actions on climate change.